The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1208/s12249-015-0463-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Once-Daily Controlled Porosity Osmotic Pump of Tapentadol Hydrochloride

Abstract: Abstract. The present study aimed to prepare, optimize, and evaluate Tapentadol hydrochloride controlled porosity osmotic pump (CPOP) and to achieve the drug release at nearly zero-order. The CPOP was prepared by the coating of polymers (Eudragit RSPO and RLPO) on a directly compressed core tablet. A Box-behnken experimental design was applied to optimize the parameters for CPOP. The optimized batch was characterized for in vitro drug release study, effect of pH, osmolarity and agitation intensity, and surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This suggests that there is no curvature effect and that the steepest ascent method can be used for optimization simulation. The present analysis confirmed the release mechanism as osmotic-activated drug release [26].…”
Section: Optimization Of Formulation For Eop Tabletssupporting
confidence: 82%
See 1 more Smart Citation
“…This suggests that there is no curvature effect and that the steepest ascent method can be used for optimization simulation. The present analysis confirmed the release mechanism as osmotic-activated drug release [26].…”
Section: Optimization Of Formulation For Eop Tabletssupporting
confidence: 82%
“…(0 atm) no sucrose, (15 atm) 201.78 g/l of sucrose, (30 atm) 402.6 g/l of sucrose, and (45 atm) 605.34 g/l of sucrose. For formulation, FT3A, dug release studies were conducted using the above media [26]. It can be suggested from the fig.…”
Section: Target Formulationsmentioning
confidence: 99%
“…For a better understanding of the influence of input variables X 1 , X 2, and X 3 , on drug release, the total number of trial batches was grouped based on sodium chloride concentration, as shown in Figure 3A-D. Thakkar et al also grouped dissolution data of trial formulations based on different osmogen levels. 37 Burst release was observed from the comparison of drug release profile of low level (−1) group F-7, and F-13, whereas F-5, F-9, and F-18, failed to meet the recommended criteria of osmotic tablets %CDR 6 and 12 hours ( Figure 3A). Burst effect was also observed for the mediumlevel group F-4 and F-11 ( Figure 3B) and high-level group F-2 and F-20 ( Figure 3C).…”
Section: In Vitro Drug Release Studymentioning
confidence: 98%
“…There are three mechanisms that contribute to the release of active material from controlled porosity osmotic pump i.e., drug release driven by the mechanism of osmotic pressure, size and number of pores formed in the membrane and water uptake of the membrane. To demonstrate the role of osmotic pressure for drug release, the optimized formulation of controlled porosity osmotic pump was subjected to in vitro drug release study in different concentrations of NaCl (0.5, 1 and 2 mol/l) used as dissolution medium [11].…”
Section: Investigation Of Drug Release Mechanismmentioning
confidence: 99%